In vitro influence of dietary protein and fructooligosaccharides on metabolism of canine fecal microbiota. Issue 1 (December 2016) - Pinna, Carlo; Vecchiato, Carla; Zaghini, Giuliano; Grandi, Monica; Nannoni, Eleonora; Stefanelli, Claudio; Biagi, Giacomo
Abstract Background The present in vitro study investigated whether the utilization of fructooligosaccharides (FOS) may influence canine fecal microbial population in presence of diets differing in their protein content and digestibility. Fresh fecal samples were collected from five adult dogs, pooled, and incubated for 24 h with the undigested residue of three diets: 1, Low protein high digestibility diet (LP HD, crude protein (CP) 229 g/kg); 2, High protein high digestibility diet (HP HD, CP 304 g/kg); 3, High protein low digestibility diet (HP LD, CP 303 g/kg) that had been previously subjected to enzymatic digestion. In the in vitro fermentation study, there were six treatments: 1) LP HD; 2) HP HD 3) HP LD; 4) LP HD + FOS; 5) HP HD + FOS; 6) HP LD + FOS. Fructooligosaccharides were added at the final concentration of 1.5 g/L. Samples of fermentation fluid were collected at 6 and 24 h of incubation. Results Values of pH were reduced by FOS at 6 and 24 h (P  < 0.001); conversely, low protein digestibility and high dietary protein level resulted in higher pH at both sampling times (P  < 0.001). At 24 h, FOS lowered ammonia (−10 %;P  < 0.001) and resulted (P  < 0.05) in higher concentrations of total volatile fatty acids (VFA) (+43 %), acetic acid (+14 %), propionic acid (+75 %) andn -butyric acid (+372 %). Conversely, at 24 h, low protein digestibility resulted (P  < 0.01) in lower concentrations of acetic acid (−26 %), propionic acid (−37 %) and total VFA (−21 %). Putrescine concentrations were increased at 6 and 24 h of fermentation by low protein digestibility (+21 and 22 %, respectively;P  < 0.05) and FOS (+18 and 24 %, respectively;P  < 0.01). After 24 h of fermentation, high dietary protein level resulted in lower counts of lactobacilli and enterococci (−0.5 and −0.7 log cells/mL, respectively;P  < 0.05) whereas low protein digestibility tended to increase counts ofC. perfringens (+0.2 log cells/mL;P  = 0.07). Conclusions Results from the present study showed that diets rich in protein may exert negative influences on the canine intestinal ecosystem, slightly increasing the presence of ammonia and reducing counts of lactobacilli and enterococci. Moreover, the presence of poorly digestible protein resulted in lower concentrations of VFA. Conversely, administration of FOS may improve metabolism of canine intestinal microbiota, reducing ammonia concentrations and enhancing VFA production.